Macronutrient and micronutrient intake in stunted children: The role of household food insecurity - Purwanti, Rachma; Arfinanda, Najwa Diva Khoirunnisa'; Laura, Cicilia; Susilo, Mursid Tri; Syauqy, Ahmad; Noer, Etika Ratna; Wijayanti, Lilis (Diversity: Disease Preventive of Research Integrity, 2026)
Insufficient nutrient intake remains a persistent determinant of child stunting, yet evidence mapping macro–micronutrient intake against household food insecurity in Indonesian urban settings is limited. This study addresses this gap by correlating nutrient intake with HFIAS scores among stunted children in Semarang. This cross-sectional study included 82 stunted children in Semarang, Indonesia. Household food insecurity was assessed using the Household Food Insecurity Access Scale (HFIAS), while macronutrient and micronutrient intakes were estimated using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Data normality informed the use of Pearson or Spearman correlation tests for bivariate analysis. Overall, 61% of households were classified as food-insecure, and most children exhibited inadequate carbohydrate intake and deficiencies in vitamin A and vitamin C. HFIAS scores were significantly correlated with carbohydrate intake (p=0.006; r=0.300) and iron intake (p=0.033; r=0.235), indicating higher food security was associated with higher intake, while no significant correlations were observed for energy, protein, fat, calcium, zinc, vitamin C, vitamin A, or vitamin B12. These findings support integrated family-based interventions combining supplementary feeding (PMT) with strategies to strengthen household food access and affordability. Programmatically, embedding Islamic values, such as amanah (shared responsibility for child wellbeing), halal–tayyib dietary guidance, and community solidarity through zakat/infaq based support that may enhance sustainable family nutrition and food security in urban contexts.